2009
DOI: 10.1111/j.1365-313x.2008.03706.x
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan deficiency affects organ growth by retarding cell expansion in Arabidopsis

Abstract: SummaryTryptophan (Trp) is an essential amino acid required not only for protein synthesis but also for the production of many plant metabolites, including the hormone auxin. Mutations that disrupt Trp biosynthesis result in various developmental defects in plant organs, but how Trp affects organ growth and development remains unclear. Here, we identify an Arabidopsis mutant, small organ1 (smo1/trp2-301), which exhibits a reduction in the size of its aerial organs as a result of the retardation of growth by ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 61 publications
1
62
0
Order By: Relevance
“…Using a nonlethal deficiency mutant, a crucial role for His homeostasis in root meristem maintenance has been demonstrated (Mo et al, 2006). Also, it has been shown that Trp deficiency produces retardation of aerial organ development by affecting cell expansion in Arabidopsis (Jing et al, 2009). By reducing the content of Ser in gapcp double mutant roots, a drastic arrest of its development was observed.…”
Section: Gapcp Activity Is Critical For Ser Biosynthesis In Rootsmentioning
confidence: 99%
“…Using a nonlethal deficiency mutant, a crucial role for His homeostasis in root meristem maintenance has been demonstrated (Mo et al, 2006). Also, it has been shown that Trp deficiency produces retardation of aerial organ development by affecting cell expansion in Arabidopsis (Jing et al, 2009). By reducing the content of Ser in gapcp double mutant roots, a drastic arrest of its development was observed.…”
Section: Gapcp Activity Is Critical For Ser Biosynthesis In Rootsmentioning
confidence: 99%
“…It has been previously shown that tryptophan synthase mutants can be rescued by externally supplied L-tryptophan (L-Trp) (Jing et al, 2009;Last et al, 1991;Last and Fink, 1988;Müller and Weiler, 2000). We therefore examined trp2-12 mutants grown on medium supplied with 10 μM L-Trp and found that the mutant phenotypes, including phloem unloading and xylem patterning defects, were completely rescued (supplementary material Fig.…”
Section: Isolation Of Mutants With Reduced Hd-zip III Expression and mentioning
confidence: 99%
“…Therefore, an alternative hypothesis is that the severe retardation of plant growth and the reticulate leaf phenotypes in ipgam double mutants are not due to reduced energy provision but rather to altered aromatic acid metabolism. Several reticulate leaf mutants have been characterized recently, including cue1 (Voll et al , 2003), ven3 and ven6 (Molla-Morales et al , 2011), and trp2 (Jing et al , 2009). Analysis of these mutants suggests that mesophyll development is restricted and amino acid biosynthesis is impaired.…”
Section: Discussionmentioning
confidence: 99%